2009
DOI: 10.1075/jhp.10.1.03pre
|View full text |Cite
|
Sign up to set email alerts
|

Empowerment and disempowerment in the Glencairn Uprising

Abstract: The Glencairn Uprising (1653-1654) was a military rebellion by Scottish Highlanders under the leadership of William, Earl of Glencairn, against the English government of Oliver Cromwell. This paper investigates the presentation of actors and groups on both sides of the Uprising -but most especially Glencairn himself -in the contemporary London press. The theoretical framework of the analysis is Critical Discourse Analysis (modelled especially on the approach of van Dijk 1991); however, a corpus-based methodolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…; Mulderrig (2008); O' Halloran (2008); Taylor (2009); Prentice & Hardie (2009); Augoustinos et al, (2010), Freake et al, (2011), and Subtirelu (2013).…”
mentioning
confidence: 99%
“…; Mulderrig (2008); O' Halloran (2008); Taylor (2009); Prentice & Hardie (2009); Augoustinos et al, (2010), Freake et al, (2011), and Subtirelu (2013).…”
mentioning
confidence: 99%
“…This article has demonstrated that there are a number of resources available for the representation of women in this corpus of seventeenth-century quasi-legal discourse, and provides further support for the applicability of combining Critical Discourse Analysis and Corpus Linguistics theory and method to historical corpora (see also Prentice and Hardie 2009). A straightforward comparison of the most frequent collocates of the generic terms man, men, woman and women provided the point of departure for an examination of the lexico-grammatical choices that contribute to an overall impression of the identity of women in the Depositions, and their role in reported events.…”
Section: Discussionmentioning
confidence: 93%
“…the text's relationship with other texts, and other types of text. It has been suggested elsewhere that such practices in relation to historical data are largely inaccessible (Prentice and Hardie 2009). However, we do have the information that the Depositions are written records of spoken testimony, recorded by scribes with the authority of commissioners employed by the government.…”
Section: Critical Discourse Analysismentioning
confidence: 98%
See 1 more Smart Citation
“…These strategies tend to portray the Ribbonmen and the beneficiaries in a positive light, while the targets on the "them" side are portrayed more negatively, similar to the English and the Scots in Prentice and Hardie (2009) The analysis has shown that the sending of the notices involved a pervasive element of legitimisation. The depiction of the targets, frequently landlords and agents, as tyrannical, criminal and unjust functions to establish the moral superiority of the senders of the notices over them.…”
Section: Discussionmentioning
confidence: 99%